The growth and yield response of several maize (Zea mays L.) genotypes against the application of bioslurry liquid fertilizer - Ediwirman, Edi Ediwirman; Ermawati, Erma Ermawati; Andini, Del Delmita (Universitas Muhammadiyah Mataram, 2025)
Bioslurry liquid fertilizer is one of the biogas wastes that has been utilized in improving soil fertility. Free-range maize has the potential to support increased production alongside hybrid maize. The study aimed to assess the role of bioslurri liquid fertilizer for the growth and yield of several genotypes of maize plants. The research was conducted on dry land in Nagari Batang Betung, Basa Ampek Balai Tapan District, Pesisir Selatan Regency from Juny to October 2023. The research used a factorial completely randomised design (CRD). The first factor was maize genotype consisting of; Sukmaraga and Bisma varieties, JK, and JM line. The second factor was bioslurri liquid fertiliser (ml/L water) with 3 levels namely: 0, 50, and 100. The observed variables were plant height, male flowering age, female flowering age, root length, root dry weight, top dry stover weight, cob length, cob diameter, cob dry weight, 100 seed weight, and dry kernel weight per ha. Data were statistically analyzed with F test and Duncan's further test at 5% real level. Data were analyzed using Statistix ver. 8. The study showed that there were no interaction of bioslurri liquid fertilizer on the growth and yield of several genotypes of corn plants, and bioslurri liquid fertiliser also had no significant effect on the growth and yield of maize. Strain JK produced better growth in height, cob length, 100-seed weight, and dry kernel weight per ha than strains JM, varieties Sukmaraga and Bisma. The dry kernel weight of JK strains reached 4.90 tonnes/ha. Line JK can be used as candidate for new maize high-yielding varieties of free-range maize.